Determinants of Cultural Tourism Engagement: An In-depth Analysis of Tea Culture Tourism at Wuyi Mountain, Fujian Province, China - Cai, Yilin; Jiang, Songyu (Jurnal Toursci, 2024)
We aim to uncover factors affecting tourists’ intention to visit Wuyi Mountain as a tea culture tourism destination. This study utilized a questionnaire survey method to collect 403 Generation Z tourists from Beijing, Shanghai, and Shenzhen. Furthermore, this research conducts a structural equation model to process the data. The results indicate (1) Cultural identity has a direct positive impact on behavioral intentions, indicating that the stronger the sense of cultural identity, the stronger the tourists' behavioral intentions; (2) Attitude, subjective norms, and perceived behavioral control also have direct positive impacts on the behavioral intentions of Generation Z tourists, suggesting that these factors play essential roles in the formation of behavioral intentions; (3) Cultural identity indirectly influences behavioral intentions through attitude, subjective norms, and perceived behavioral control, with these factors serving as significant mediators between cultural identity and behavioral intentions.